Antivenomic assessment of the immunological reactivity of EchiTAb-Plus-ICP, an antivenom for the treatment of snakebite envenoming in sub-Saharan Africa. - Calvete, J; Cid, P; Sanz, L; Segura, A; Villalta, M; Herrera, M; León, G; Harrison, R; Durfa, N; Nasidi, A; Theakston, R; Warrell, D; et al. (2010)
The immunoreactivity of EchiTAb-Plus-ICP, an antivenom developed for the treatment of snakebite envenoming in sub-Saharan Africa, to venoms of seven Echis and Bitis species, was assessed by "antivenomics." This proteomic approach is based on the ability of an antivenom to immunodeplete homologous or heterologous venom proteins. Our results show an extensive cross-reactivity of this antivenom against all Echis and Bitis venoms studied, as revealed by the complete immunodepletion of the majority of venom components, including metalloproteinases, serine proteinases, C-type lectin-like proteins, some phospholipases A(2) and L-amino acid oxidase. However, some phospholipases A(2), disintegrins and proteinase inhibitors were immunodepleted to only a partial extent. These results support the hypothesis that immunizing horses with a mixture of the venoms of Echis ocellatus, Bitis arietans, and Naja nigricollis generates antibodies capable of recognizing the majority of components of medically-relevant homologous and heterologous viperid venoms of the genera Bitis and Echis from sub-Saharan Africa.